2015
DOI: 10.1016/j.jhealeco.2014.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Medicaid expansions for the working age disabled: Revisiting the crowd-out of private health insurance

Abstract: Disabled individuals under 65 years old account for 15% of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…To improve upon earlier work, I employ an alternative method of identifying cost shifting that avoids using a change in the reimbursement rate and also measures cost-shifting from a Medicaid perspective. I take advantage of a unique Medicaid expansion described in Wagner (2015). The Omnibus Reconciliation Act of 1986 (OBRA86) gave states the authority to increase Medicaid income more than 74.73 percent.…”
Section: Research Strategymentioning
confidence: 99%
See 3 more Smart Citations
“…To improve upon earlier work, I employ an alternative method of identifying cost shifting that avoids using a change in the reimbursement rate and also measures cost-shifting from a Medicaid perspective. I take advantage of a unique Medicaid expansion described in Wagner (2015). The Omnibus Reconciliation Act of 1986 (OBRA86) gave states the authority to increase Medicaid income more than 74.73 percent.…”
Section: Research Strategymentioning
confidence: 99%
“…3 The goal of this paper is to test the cost-shifting hypothesis by exploiting recent Medicaid expansions for individuals with disabilities that reduced the average revenue per patient received by hospitals. Wagner (2015) demonstrated that these Medicaid expansions led to 100 percent crowd-out of private health coverage among the disabled population. Crowd-out occurs when newly eligible individuals with private health insurance drop their current health plans in favor of public coverage through Medicaid.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pines et al (2016) and Moghtaderi, Black, Zocchi, & Pines, (2020) found a relative drop in privately insured ED visits in expansion states after ACA Medicaid expansion. Wagner (2015) reported that Medicaid expansions led to nearly 100% crowd out of private insurance for disabled persons who became Medicaid eligible. Johnston, McMorrow, Thomas, and Kenney (2020) report evidence of crowd out among new low‐income mothers who become Medicaid‐eligible under the ACA.…”
Section: Introductionmentioning
confidence: 99%